Chemical and physical characterization of samosas with shiitake mushroom - Guiné, Raquel (2018)
Owing to the increasing demand for shiitake mushrooms, a substantial amount of by-products is produced on a daily basis. Hence, to investigate ways to value this resource is of wide interest. In that way, the aim of this work was to develop new valued foods incorporating shiitake mushroom, to utilize the products that do not comply with standards for commercialization, thus avoiding waste. For this, a filling for samosas was produced and the final products were analyzed for their chemical composition, color, texture and sensorial attributes. The results showed that the shiitake samosas had a somewhat balanced chemical composition, with protein and minerals, but not forgetting fat, present due to the frying operation. The color varied between samples, although on average both sides of the samosas were of practically the same color. The textural measurements indicated that the shiitake samosas were soft and with low chewiness, with moderate resilience and cohesiveness and high springiness. The sensory panel appreciated both the dough and the filling, as well as the whole shiitake samosas, by attributing them high scores (about 4, on a scale from 1 to 5). Finally, some significant correlations were found between some specific sensorial evaluations and instrumental measurements.